Attitudes Toward Migrants in a Highly Impacted Economy: Evidence From the Syrian Refugee Crisis in Jordan. (January 2021) - Alrababa'h, Ala'; Dillon, Andrea; Williamson, Scott; Hainmueller, Jens; Hangartner, Dominik; Weinstein, Jeremy
With international migration at a record high, a burgeoning literature has explored the drivers of public attitudes toward migrants. However, most studies to date have focused on developed countries, which have relatively fewer migrants and more capacity to absorb them. We address this sample bias by conducting a survey of public attitudes toward Syrians in Jordan, a developing country with one of the largest shares of refugees. Our analysis indicates that neither personal- nor community-level exposure to the economic impact of the refugee crisis is associated with antimigrant sentiments among natives. Furthermore, an embedded conjoint experiment validated with qualitative evidence demonstrates the relative importance of humanitarian and cultural concerns over economic ones. Taken together, our findings weaken the case for egocentric and sociotropic economic concerns as critical drivers of antimigrant attitudes and demonstrate how humanitarian motives can sustain support for refugees when host and migrant cultures are similar.